تجليات الفضاء المفتوح في ميمية حُميد بن ثور الهلالي (دراسة العناصر القصصية في القصيدة) - الديوب سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى دراسة العناصر القصصية في ميمية حُميد بن ثور الهلالي من خلال دراسة تجليات الفضاء في هذه القصيدة، وقد بلغت مئة وخمسة وثمانين بيتاً، ظاهرها تنوع في الموضوعات، لكن هذه الموضوعات المتنوعة مرايا موافقة لحال شعورية واحدة انتابت الشاعر هي الحنين إلى المرأة التي أحب. وقد عبر عن هذا الحنين بقصص شعرية جمعت معظم أركان القصة المعاصرة من حوار، وحدث، وعقدة، وحل، وشخصيات وزمان، ومكان. وتحوي هذه القصيدة عناصر قصصية ، ولايمكن أن ننظر إليها على أنها قصيدة قصصية صرف. أما مصطلح الفضاء (Space) فقد ترجم إلى العربية، وأصابه ما أصاب غيره من المصطلحات من فوضى في التسمية، فالتبس بمفهوم المكان والحيز، وهو مصطلح تناوله النقد الروائي أولاً. وقد تجلى الفضاء في هذه القصيدة بأشكال مختلفة. فثمة فضاء اجتماعي، وطبيعي، ودلالي، وثمة فضاء ثقافي فتح باباً للقول لدى الشعراء، فثمة جوانب فريدة في هذه القصيدة أسست معاني تداولها الشعراء فيما بعد. This research aims at studying the narrative elements in al-Mimiyah of Homaid Bin Thaur Al-Helali by studying the manifestation of open space in this poem. The poem consists of one hundred and eighty five lines which appear to be of diverse subjects; but these subjects in reality are mirrors of a one emotional state of the poet, which can be defined as longing for the woman he loved. He expresses his longing with the use of poetic narratives that compiled most of the present-day narrative techniques such as: dialog, event, plot, solution, characters, time and place. We can say that it is a mere poem. The term “Space” was translated into Arabic, and it has miss in translation such as other translated terms, the term “space” has been confused with the term “place” which is, for instance, a term of narrative criticism. Space appears in the poem in different ways: social space, natural space, denotative space, culture space which creates a wide area for criticism. There are unique sides in this poem, which create innovate meanings that poets have used later on.